Exploring the Association between Maternal Mood and Self‐Reports of Sleep during the Perinatal Period. Issue 4 (19th June 2014) - Coo, Soledad; Milgrom, Jeannette; Kuppens, Peter; Cox, Pauline; Trinder, John
ABSTRACT Objective To explore the psychological mechanisms involved in the close association between maternal mood and self‐reports of sleep quality during the perinatal period using appraisal theory of emotions. Design Repeated measures. Setting Antenatal clinics of a health center associated with the Northern Hospital in Melbourne, Australia. Participants 122 pregnant women in their third trimester of gestation. Methods Participants completed the Pittsburgh Sleep Quality Index (PSQI), the Edinburgh Postnatal Depression Scale, and an appraisal questionnaire during the third trimester of gestation, within 7 to 10 days after childbirth, and at 10 to 12 weeks postpartum. Correlational and regression analyses were used to explore the associations between sleep reports and appraisals. Results Self‐reports of poor sleep quality, impaired daytime dysfunction due to poor sleep, and the global PSQI score were associated with a low perceived ability to cope practically and emotionally with motherhood‐related issues as well as with negative expectations about the future. Conclusions Appraisal dimensions associated with self‐reports of poor sleep quality are similar to those related to maternal distress identified by previous research. This finding contributes to a better understanding of the association between self‐reports of sleep and maternal mood. Practical implications are discussed.